POPULASI DAN SERANGAN HAMA ULAT KANTUNG Metisa plana Walker (Lepidoptera; Psychidae) SERTA PARASITOIDNYA DI PERKEBUNAN KELAPA SAWIT KABUPATEN DONGGALA, SULAWESI TENGAH - Ronny Pamuji; Bambang Tri Rahardjo; Hagus Tarno (Universitas Brawijaya, 2013)
ABSTRACTThis research was aimed to study the population, attack intensity of bagworm (M. plana) and it parasitoid on oil palm plantations. Sampling was conducted 4 times in blocks 1-9 Afdeling OK PT. Lestari Tani Teladan, Donggala, Central Sulawesi from August to October 2012. A systematic sampling method was used to observe M. plana population from each observation point. There were two stages of M. plana such as larvae and pupae. Both stages were checked their conditions to clarify their parasitoids. In addition, parasitoids were observed especially at fourth observation. Result showed that population of M. plana larva decreased during observation period (from August to October 2012). Opposite condition was occurred that population of pupa increased in same period of observation. Highest population of M. plana was recorder on third and fourth block of plantation. Number of parasitized pupae directly proportional to total of pupae (R2=0,95). Populations of parasitoid have not been able to control pests M. plana naturally. Some parasitoids were identified such as Brachymeria sp. (34%), Eurytoma sp. (13%), Entodoninae (17%), Tetrastichus sp. (24%), Tachinidae 9% and two species of Phygadeuontinae 2% and 1% for each.Key words: bagworm, Metisa plana, parasitoid, oil palm